Características geotécnicas dos depósitos de argila mole do recife a influência da matéria orgânica - Teixeira, Dilson Corrêa Lima (1972)
The origin and formation of Recife plain is reviewed in an introductory manner, and thereby the main foundation soil problems described. Main concern is the influence of organic matter into the Atterberg limits, natural moisture content, specific gravity and grain size analysis of dark grey to black soft organic clays from subsoil of Recife plain. No previous work has been registred for this region. Samples were treated in two different ways for the identification tests and mineralogical analysis (X-Ray Diffraction and Differential Thermal Analysis): oven-dried at 105ºC and normal atmospheric pressure, or oven-dried at 45ºC and - 25" Hg vacuum. Quite large differences of results (up to 30%) were obtained. Grain size analysis also seem to be affected by amount of organic matter; the clay percentage increases with organic matter content, even for same plasticity values. Through DTA the organic matter was disclosed comparing results obtained with pretreated samples and with normal samples. Shearing strength of shelby samples 41,2 mm (1 5/ 8") - diameter were obtained through triaxial tests and unconfined compression tests. Also inplace vane shear tests were performed in 75 mm (3") - casing and 63,5 mm (2 1/2") vane. Unconfined compression and vane tests show that clays are generally sensitive and exceptionally extrasensitive at some depth locations.